PEMBUATAN DAN EVALUASI KARAKTERISTIK FISIK HAND AND BODY LOTION DARI KOMBINASI EKSTRAK BUNGA LAVENDER (Lavandula angustifolia Mill) DAN EKSTRAK BATANG SEREH (Cymbopogon citratus (DC) Stapf) - Samosir, Sri Rezeki; Samgryce, Hartika; Husna, Miftahul (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
Hand and body lotion from a combination of lavender flower extract (Lavandula angustifolia Mill) and lemongrass stems (Cymbopogon citratus (DC) Stapf) has been carried out. The research method is experimental in the laboratory with a quantitative analysis approach. The samples from this research were extracts from lavender flowers and lemongrass stems. The research stages include sample sorting, extraction, extract evaporation, making hand and body lotion and evaluating the characteristics of hand and body lotion. The extraction stage used the maceration method for 3 days with 96% ethanol solvent, the extract obtained was concentrated using a rotary evaporator. Hand and body lotion from a combination of lavender flower extract and lemongrass stems is made in 3 concentrations, namely 1%, 3% and 5% respectively. Tests evaluating the physical characteristics of the preparation include organoleptic tests, homogeneity tests, pH tests, spreadability tests, hedonic tests, irritation tests on volunteers and viscosity tests. The organoleptictest results showed that the preparation hadagreenish brown color and a smooth texture. Based on the results, it can be concluded that a combination of lavender flower extract and lemon grass stem extract can be formulated in hand and body lotion preparations. It is recommended that researchers further make other cosmetic preparations such as facial lotion from lavender flower extract and lemongrass stem extract.